Secondary school teachers' competence in educational assessment of students in Bahir Dar town - Lake Bedilu (College of education, Bahir Dar University, 2023)
The purpose of this study was to assess the competence of secondary school teachers in the educational assessment of students among secondary schools in Bahir Dar town. To do so, a sample of 60 secondary school teachers in Bahir Dar town was taken. A questionnaire adapted from Plake, Impara and Fager's (1993) was used to collect data. The questionnaire was composed of 31 multiple-choice items used to assess teachers' competence in the educational assessment of students. Descriptive statistics and t-test was used to determine whether there exists a significant difference in teachers' competence based on differences in the school type where teachers taught. It was found out that teachers participating in this study demonstrated knowledge rated below average in the educational assessment of students. Across the seven competency areas, teachers showed low level of competency with minor differences. Finally, teachers in the nongovernmental schools had a significantly higher level of competence than teachers who taught at governmental schools at a < 0.05. The findings suggest that, it is time for the education community to recognize that teachers are incompetent to successfully undertake student assessment. This is especially most important due to the current trend in student assessment, involving continuous assessment strategies that require more knowledge and skill about assessment. Unless corrective measures are taken to improve this poor competence of teachers in the educational assessment of students, the poor quality of education that exists currently will get much worse and the whole educational process might 'collapse'.